Improving the Education Quality for Children in Dumpit, Tangerang Region - Debora Suryani Sitinjak; Kelly Sinaga; Friska Purba; Candra Tahya (Institute for Research and Community Services, 2019)
The biggest hope for a better life in our society is through good quality of education. Through education, everyone will also be exposed to the truth. The tutoring program reported in this paper attempted to improve the quality of education for children in Dumpit, Tangerang. There were a great number of children who were not able to to go to school due to their parents’ difficult situation. In addition, these children’s parents paid little attention to their children’s physical appearance, health care, and behaviors. Through this tutoring activity, the students were exposed to the importance of education, moral and characters, and healthy living. Some materials given to the early age students included basic calculating, writing, reading, and singing. For elementary students, they were tutored in math, science, language, arts, civilization, and social science. For secondary level students, they were tutored in math, physics, biology, chemistry, accounting, language, economics, geography, sociology, history, and civilization. The mentoring methods used varied depending on the number of students and their characteristics. The mentors did their best to make learning active and fun so that the students did not get bored. We hope that this tutoring program is beneficial to the students and might have a good impact on the students and their neighborhood as well as the tutors.